"Forever family is like a manufactured Hallmark idea": Adoption discontinuity experiences of intercountry adoptees. (August 2022) - Kim, JaeRan
Abstract: Background: Media stories over the past decade have sensationalized cases of intercountry adoption discontinuity, a phenomenon largely missing from the research literature. Objective: This study sought to understand how intercountry adoptees with adoption discontinuity histories experience legal, relational, and residential permanency losses through the framework of ambiguous loss and trauma. Participants and setting: Twenty intercountry adoptees in the United States who experienced adoption discontinuity as minor children. Methods: Participants were recruited through social media sites and professional and informal organizations serving intercountry adoptees. Results: Participants described multiple experiences with legal, residential, and relational permanency losses often in multiple combinations, multiple times, and in multiple settings. Participants also experienced racial, ethnic and cultural identity losses in addition to their permanency ruptures. Conclusion: More research on the lived experiences of intercountry adoptees with adoption discontinuity histories is needed. Adoptees experience trauma in their pre-adoptive histories as well as in the adoption process itself and need adoptive parents skilled in trauma-informed parenting. In addition, there is a need for robust trauma-informed support for adoptees throughout their lifetime. Highlights: Intercountry adoptees with adoption discontinuity experiences experience legal, residential, relational, and cultural losses Adoption disruptions, displacements and dissolutions lead to additional trauma and sense of ambiguous loss Disruption to childhood adoption placements may lead to residential, relational, and cultural instability in adulthood